Regional Volatility Linkages: Impact of Neighbouring Currencies on Nigeria’s Currency Instability - Babalola, Abdurrauf; Muhammad, Kudu Ibn (Analiza związków zmienności regionalnej: wpływ sąsiednich walut na niestabilność waluty Nigerii, 2024)
This study examines the effect of the exchange rate volatility of currencies of countries bordering Nigeria, namely the Benin Republic, Niger, Chad and the Cameroon Republic on Nigeria's exchange rate volatility using monthly observations for 1st January 2001 to 31st December 2021. The study employed the Generalised Auto-Regressive Conditional Heteroscedasticity method to analyse the dataset. The study found that fluctuations in the currencies of these countries have a significant impact on the volatility of Nigeria's currency naira. As a result, it is recommended that policymakers and government agencies strengthen security along the Nigeria-Cameroon, Nigeria-Benin, Nigeria-Chad, and Nigeria-Niger borders to more strictly regulate imports and support the stability of Nigeria's currency. The Nigerian government should encourage less importation from these countries through import-substitute production and higher exportation from Nigeria as such could lead to the appreciation of the naira.
Econometrics = Ekonometria, 2024, Vol. 28, No. 1, s. 11-25
Keywords: ARCH; bordering counties currency; exchange rate volatility; GARCH; waluta powiatów graniczących; zmienność kursu walutowego